0630 A 4-Week Sleep Intervention that Advances and Stabilizes Sleep Timing Leads To Meaningful Improvements in Pain and Physical Function in People With Fibromyalgia. (25th May 2022) - Burgess, Helen; Bahl, Sonal; Wilensky, Katelyn; Spence, Emily; Jouppi, Riley; Rizvydeen, Muneer; Goldstein, Cathy; Williams, David; Kim, Myra; Burns, John
Abstract: Introduction: Fibromyalgia is characterized by chronic widespread pain, mood and sleep disturbance, and affects over 20 million Americans. Pharmacological treatments (antidepressants, antiepileptics, opioids) often have small treatment effects and adverse side-effects. Exercise therapy requires significant patient motivation, and psychotherapy requires specialized personnel. Here we report on a randomized clinical trial in which we tested a 4-week sleep-wake scheduling intervention with either a dim or bright daily 1 hour morning light treatment. Methods: Fifty-four adults (52 females, 18-78 years) meeting ACR 2011 diagnostic criteria for fibromyalgia completed a 5-week protocol. In the first week each participant slept at home, ad lib, on their usual sleep schedule. Thereafter, they followed a fixed sleep schedule and a daily 1-hour morning light treatment (randomized to dim or bright light). The sleep schedule advanced each participant's individual sleep-wake timing by no more than 1 hour, and focused on stabilizing sleep timing. Participants were monitored with wrist actigraphy throughout the study. Outcomes were assessed at baseline, 2 weeks and 4 weeks after the intervention. Results: The 4-week intervention resulted in an average 36-minute advance in participants' sleep timing in both groups (ps<0.001). Night-to-night variability in sleep timing also significantly decreased in both groups (ps<0.01). Pain and physical function improved equally in both groups (Fibromyalgia Impact Questionnaire-Revised, PROMIS Pain intensity, PROMIS Physical Function, ps<0.01). Across both groups, a greater shift in morningness (Owl-Lark score) was associated with a greater reduction in depressive symptoms (PHQ-9; r=-0.45, p<0.001). No significant side effects were reported in either group. Treatment expectations were not significantly correlated with symptom improvement (all rs nonsignificant). Conclusion: Results suggest that 4 weeks of an advanced and stabilized sleep schedule can lead to meaningful improvements in pain and physical function in people with fibromyalgia. The addition of a bright vs. dim morning light treatment did not further increase symptom improvement. A reduction in depressive symptoms during the intervention may have contributed to the improvements in pain and physical function. Sleep-wake scheduling should be further explored as a potentially feasible, acceptable and effective adjunctive non-pharmacological treatment for fibromyalgia. Support (If Any): Grant awarded from NINR R21 NR016930.